Verticillium dahliae-eggplant as the pathosystem model to reveal biocontrol potential of three Trichoderma spp in green house conditions (Atlas Journal of Biology, 2018)
In this study three Trichoderma species isolated from Moroccan soil (natural and agricultural habitats) were investigated for their biocontrol potential against virulent Verticillium dahliae on eggplant in green house conditions based on dipping root approach. Evaluation of biocontrol efficacy of Trichoderma spp. demonstrated effective potential of Trichoderma on reducing Verticilium disease on eggplant cultivars. Disease assessment was established by measuring disease incidence in root units (DI-RU) and in the above ground of eggplant cultivars (DI- AU). DI-RU% was recorded at 12.5%, 25.0%, 31.3% and 37.5% in T3, TC, T1 and T2 treatment respectively where DI-RU recorded in Tm2 controls; eggplants inoculated with Verticillium only was equal to 100.0%. Whereas, disease incidence outcomes in aerial part was DI- AU = 100.0 % in treatments TC and T2, 87.5% in T1 and 96.0% in T3 treatment where Tm2 controls were assessed with 100.0%.